How do lesions affect limb lengthening in children with Ollier’s disease? - Chunxing Wu; Peng Huang; Yueqiang Mo; Dahui Wang; Bo Ning (BMC Musculoskeletal Disorders)
Abstract Purpose Ollier’s disease (multiple enchondromatosis) can cause severe lower limb length discrepancy and deformity in children. Osteotomy and limb lengthening with external fixation can correct the lower extremity deformity. There may be lesions in the osteotomy part (OP), and the internal fixation part of the external fixation(FP). This study aimed to evaluate: (1) whether lesions in OP and FP influence the lengthening length, speed, and deformity correction; (2) the number of intact sides of the OP and FP that are necessary to provide enough stability to achieve the lengthening correction aim. Methods Fifteen children with Ollier’s disease underwent treatment of 21 lower limb segments using distraction osteogenesis. All osteotomies were performed at the center of rotation and angulation, resulting in a total of fourteen OP intralesionally and nineteen FP intralesionally. The lengthening length, speed, and correction of angular deviation were compared in different groups (lesions vs. non-lesions in OP /FP). Results Full correction of the deformity and full restoration of length were achieved in all cases. There were no significant differences between intralesional (14 cases) and extralesional (7 cases) distraction groups in new bone formation speed (OP). Although 19/21 of the FP were inserted intralesionally, all the wires and half-pins were well stabilized throughout the external fixation period. There were no significant differences between these groups in the incidence of complications, such as infection, pathological fractures, and early consolidation. Conclusions In Ollier’s disease, the stability provided by newly formed callus and the external fixation were sufficient to lengthen and correct lower limb deformities successfully, even when OP and FP were performed intralesionally with / without intact sides.